(untitled) (Conferencea, 2021)
Today, the generally accepted resolution standard is 4K, and we are moving towards 8K screens. Youtube started supporting 4K for video downloads back in 2010 — then many manufacturers began to produce inexpensive cameras in this format. Since then, displays and smart TVs with 4K support have dropped significantly in price and gained popularity. Despite the fact that the human eye can hardly physically notice the difference in a picture with a quality over 4K, the race for higher resolution continues. Owners of Ultra HD displays can most fully experience the capabilities of their screens when viewing native 4K content. And videos with a lower resolution have to be stretched to the whole screen, because, for example, images in 1080p (Full HD) contain only a quarter of the pixels of a 4K picture. You can scale the image immediately on a smart TV, in a media player, or use special programs to improve the video quality